Bawaslu's Transformation in Generating Supervision Cadres - Muhammad Ferdian; Afriva Khaidir (Science and Environmental Journal for Postgraduate, 2021)
The 2020 election was held in the context of the COVID-19 pandemic. The COVID-19 pandemic has attacked all aspects of life, including the implementation of elections, especially election supervision. Election supervision is one of the important aspects in the successful implementation of elections. To realize this success, it is necessary to involve the community in supervision. One of Bawaslu's challenges in engaging the community is the limitation in conducting electoral education in the field of supervision. Based on these conditions, Bawaslu released the Online Participatory Supervision Cadre School (SKPP) as an answer to the existing challenges. This paper aims to examine how the implementation of the Online Participatory Supervision Cadre School (SKPP) as the transformation of Bawaslu in producing supervisory cadres. The method in this paper is descriptive qualitative using the perspective of Larson and Rogers' social change perspective. Research data in the form of primary data and secondary data which are then analyzed using the technical analysis of Miles and Huberman. The results of this study explain that the transformation of Bawaslu in producing supervisory cadres consists of the Class I Cadre School for Participatory Supervision, the Cadre School for Participatory Supervision Class II, and the Online Participatory Supervision Cadre School (SKPP), and the use of technology in the Online Participatory Supervision Cadre School (SKPP).